Effects of Human Immunodeficiency Virus Status on Symptom Severity in Influenza-Like Illness in An Otherwise Healthy Adult Outpatient Cohort. (August 2021) - Colombo, Rhonda E; Schofield, Christina; Richard, Stephanie A; Fairchok, Mary; Chen, Wei-Ju; Danaher, Patrick J; Lalani, Tahaniyat N; Ridoré, Michelande; Maves, Ryan C; Arnold, John C; Ganesan, Anuradha; Agan, Brian; et al.
The impact of HIV on influenza-like illness (ILI) has been incompletely described in the era of combination antiretroviral therapy, particularly in the post-H1N1 pandemic period. This analysis informs on ILI in an otherwise healthy, predominantly outpatient cohort of adults with HIV in the USA. From September 2010 to March 2015, this multisite observational cohort study enrolled otherwise healthy adults presenting to a participating US military medical center with ILI, a subset of whom were HIV positive. Demographics, clinical data, and self-reported symptom severity were ascertained, and enrollees completed a daily symptom diary for up to 10 days. 510 men were included in the analysis; 50 (9.8%) were HIV positive. Subjects with HIV were older and less likely to be on active duty. Rhinovirus and influenza A were the most commonly identified pathogens. Moderate-severe diarrhea (p<0.001) and fatigue (p=0.01) were more frequently reported by HIV-positive men. HIV positivity was associated with higher gastrointestinal scores, but not other measures of ILI symptom severity, after controlling for age, race, military status, and influenza season. Few were hospitalized. HIV-positive subjects had more influenza B (p=0.04) and were more likely to receive antivirals (32% vs 6%, p<0.01). Antiviral use was not significantly associated with symptom scores when accounting for potential confounders. In this predominantly outpatient cohort of adult men, HIV had minimal impact on ILI symptom severity. Despite similar illness severity, a higher percentage of subjects with HIV reported undergoing antiviral treatment for ILI, likely reflecting differences in prescribing practices. Trial registration number: NCT01021098.